1997
DOI: 10.1176/ajp.154.11.1571
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Collaborative Panic Disorder Severity Scale

Abstract: The Panic Disorder Severity Scale is a simple, efficient way for clinicians to rate severity in patients with established diagnoses of panic disorder. However, further research with more diverse groups of panic disorder patients and with a broader range of convergent and discriminant validity measures is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
569
0
11

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 813 publications
(599 citation statements)
references
References 13 publications
5
569
0
11
Order By: Relevance
“…Participants who appeared eligible based on an initial telephone screen were invited for diagnostic interview (First et al, 1994) conducted by a trained clinical psychologist and confirmed by a psychiatrist. The diagnostic interview was followed by the clinician administered Panic Disorder Severity Scale (PDSS, Shear et al, 1997), which was repeated at posttreatment and follow-up by two independent raters for each patient (κ= .65-. 90).…”
Section: Recruitment and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who appeared eligible based on an initial telephone screen were invited for diagnostic interview (First et al, 1994) conducted by a trained clinical psychologist and confirmed by a psychiatrist. The diagnostic interview was followed by the clinician administered Panic Disorder Severity Scale (PDSS, Shear et al, 1997), which was repeated at posttreatment and follow-up by two independent raters for each patient (κ= .65-. 90).…”
Section: Recruitment and Patientsmentioning
confidence: 99%
“…It included the PDSS (Shear et al, 1997), a clinician-rated scale of PD severity and the Clinical Global Impression Scale (CGI; Guy, 1976) (both assessed by independent raters). Secondary measures were the Anxiety Sensitivity Index (ASI; Reiss et al, 1996), Sheehan Disability Scale (SDS; Sheehan et al, 1996), Mobility Inventory for Agoraphobia (MI-AAL; Chambless et al, 1984), and the Beck Depression Inventory (BDI; Beck et al, 1961).…”
Section: Treatmentmentioning
confidence: 99%
“…The Panic Disorder Severity Scale (Shear et al, 1997) profiles panic attacks in terms of both distress and frequency (scored on a 0-4 Likert-type scale). At our clinic, we use a Panic Attack Severity Scale (PASS) to assess the severity of orthostatic panic (O-PASS), neck-focused panic (N-PASS), and gastrointestinal panic (G-PASS) (Hinton, Chhean, Pich, Um, et al, 2006;Hinton, Pich, et al, 2004).…”
Section: Panic Attack Subtypesmentioning
confidence: 99%
“…The Panic Disorder Severity Scale (PDSS) measures the severity of core symptoms of PD. The PDSS is a fivepoint Likert scale that includes the frequency of panic attacks and limited symptom episodes, the anguish caused by these attacks, anticipatory anxiety, fear, agoraphobic avoidance, social impairment, and loss of productivity in work activities caused by panic attacks 11 (A). This scale has better diagnostic capacity for patients with agoraphobia, a sensitivity of 99%, and a specificity of 98%, yielding a LR+ of , increasing the diagnostic certainty from 5% (prevalence/ pretest probability) to 72%.…”
Section: Resultsmentioning
confidence: 99%